Principles of Street and Urban Road Space Formation in Modern Cities - Lytvynenko, Tetyana; Tkachenko, Iryna; Ilchenko, Volodymyr (International Journal of Engineering and Technology, 2018)
The work is devoted to improving the principles of streets and urban roads beautification elements placing. The classification of streets and urban roads beautification elements is structured. The principles of streets and urban roads beautification elements placing by using new spatial corridor principle simulation are improved. Streets and urban roads beautification elements according to hierarchical levels are structured. The street structural model spatial corridor with distribution in sub corridors to deploy beautification elements is constructed. The spatial corridor and subcorridors characterized by linear parameters and formulas for their determination are suggested. The methodology of comprehensive streets and urban roads beautification designing according to the offered principle is improved. Reconstruction beautification experimental design of Shevchenko Street in Poltava, Ukraine is done.Â Â